Peningkatan Peran Bahasa Indonesia di Dunia Internasional - Rostina Rostina (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of improving the function of Indonesian to become an international language is to show the nation's identity and increase the nation's competitiveness. Indonesian has the potential to become an international language because of various factors such as the positive attitude of Indonesian speakers is characterized by Indonesians' pleasure to use Indonesian and has a sense of love, pride and loyalty to the Indonesian language. The movement of the role of Indonesian in the country and the internationalization of the Indonesian language are jointly supported by the promotion of good and correct use of the Indonesian language. This promotion needs to be prioritized to maintain the existence of language as a symbol of the identity of the Indonesian nation in global life. Therefore, various efforts are made as well as hard work and cooperation between language institutions, all elements of the government and the role of the wider community are strategic steps to realize the existence and role of the Indonesian language in the international world.